Absorption properties and effects of caffeic acid phenethyl ester and its p-nitro-derivative on P-glycoprotein in Caco-2 cells and rats. (1st December 2016) - Gou, Jing; Yao, Xiaofang; Tang, Hao; Zou, Kaili; Liu, Yujia; Zuo, Hua; Zhao, Xiaoyan; Li, Zhubo
Abstract: Context: Caffeic acid phenethyl ester (CAPE), isolated from honeybee propolis, has pharmacological applications. A synthesized CAPE derivative, p -nitro-caffeic acid phenethyl ester (CAPE-NO2 ), showed similar activities with CAPE. The pharmacological activities of CAPE and CAPE-NO2 are related to their absorption properties. Objective: To understand the pharmacokinetic profiles of CAPE and CAPE-NO2 in rats and investigate the absorption mechanisms and effects on P-glycoprotein in Caco-2 cells. Materials and methods: The pharmacokinetic profiles of CAPE and CAPE-NO2 were obtained after oral administration (10 mg/kg) to rats. Transport studies of CAPE and CAPE-NO2 (5, 10, 20 μM) were performed in Caco-2 cell model. P-gp activities were assayed by rhodamine 123 cellular retention. Expression of P-gp was determined after the cells were administrated with CAPE and CAPE-NO2 (5, 20 μM) for 48 and 72 h. Results: The AUC(0− t ) of CAPE-NO2 (3239.9 ± 352 ng × h/mL) was two-time greater than CAPE (1659.6 ± 152 ng × h/mL) in rats. The P app values of CAPE and CAPE-NO2 were (4.86 ± 0.90) × 10 −6  cm/s and (12.34 ± 1.6) × 10 −6  cm/s, respectively. The accumulation of rhodamine 123 was increased by 1.3- to 1.9-fold and 1.4- to 2.3-fold in CAPE and CAPE-NO2 groups after 1 h administration, respectively. However, CAPE and CAPE-NO2 increased the P-gp levels by 2.1- and 1.7-fold, respectively. Conclusion: The absorption of CAPE-NO2 can be enhanced in rats and Caco-2 cells compared with CAPE. The two compounds are potential inhibitors of P-gp. The increased P-gp levels generated by CAPE and CAPE-NO2 played a role as a defense mechanism by limiting intracellular xenobiotic levels.